Identification of a Specific miRNA Profile in HIV-Exposed Seronegative Individuals. (1st September 2016) - Yahyaei, Sara; Biasin, Mara; Saulle, Irma; Gnudi, Federica; De Luca, Mariacristina; Tasca, Karen I.; Trabattoni, Daria; Lo Caputo, Sergio; Mazzotta, Francesco; Clerici, Mario
Abstract : Objective: MicroRNAs (miRNAs) are small noncoding RNAs involved in the posttranscriptional regulation of gene expression that play important roles in viral infections. Alterations of specific miRNAs are described in HIV infection, suggesting a role for miRNAs in pathogenesis of this disease. We verified whether a particular miRNA signature could be identified in natural resistance to HIV-1. Methods: Expression level of 84 miRNAs was analyzed by RT-qPCR in plasma and unstimulated peripheral blood mononuclear cell (PBMC) of 30 seronegative individuals repeatedly exposed to HIV-1 (HESN), 30 HIV seropositive subjects (HIV+), and 30 healthy controls (HC). Results were confirmed by individual RT-qPCR in in vitro HIV-1-infected PBMC and in their cell culture medium. Dicer and Drosha expression was analyzed in basal PBMC. Results: Whereas Dicer and Drosha expression was comparable in HESN, HIV+ and HC, several miRNAs were upregulated both in HESN and HIV+ compared with HC. Furthermore, miRNA-29a and miR-223 were upregulated in both unstimulated PBMC and plasma of HESN alone; their expression was reduced upon in vitro HIV-1 infection of HESN PBMC indicating that, upon infection, they are secreted in the extracellular milieu. These results were confirmed by individual qPCR. Conclusions: Our studies demonstrate that HIV-1 exposure modifies miRNAs expression even in the absence of productive infection. Because those miRNAs that are specifically increased only in HESN have been known to reduce HIV-1 replication, their modulation could represent an important mechanism in resistance to HIV-1 infection. Abstract : Supplemental Digital Content is Available in the Text.